Pedicularis sylvatica L. (P. Lackschewitz) - Lackschewitz, Paul (My University, 1928)
Paula Lakševica 1928. gadā Rucavā ievāktie meža jāņeglītes exikāti. / Die Exikte des Wald-Läusekraut, die 1928 in Rucava Paul Lackschewitz gesammelt wurden. / Wood lousewort's Exicts, were collected in Rucava Paul Lackschewitz in 1928. [Attēli no LU Muzeja kolekcijas Herbarium Lackschewitzi (RIG III); (BOT12097)]
Meža jaņeglīte
Keywords: Research Subject Categories::NATURAL SCIENCES::Biology::Organism biology::Plant physiology; Pedicularis sylvatica L.; Wald-Läusekraut; wood lousewort; Rucava